All Days 2008
DOI: 10.2118/114925-ms
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Petrophysical Evaluation of Shale Gas Reservoirs

Abstract: Gas shales are economically viable hydrocarbon prospects that have proven to be successful in North America. Unlike conventional hydrocarbon prospects, gas shales serve as the source, seal, and the reservoir rock. Generating commercial production from these unique lithofacies requires stimulation through extensive hydraulic fracturing. The absence of an accurate petrophysical model for these unconventional plays makes the prediction of economic productivity and fracturing success risky.This paper presents an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…For example, in the Barnett shale, the most brittle sections were found to be those rich in silica and low in clay. These compositions are generally found by core analysis (Jacobi et al, 2008). Brittleness can be determined from the Young's Modulus, Poisson's Ratio, and Brinell hardness of the shale, all of which are determined from core samples (Kundert et al, 2009).…”
Section: Prospectingmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the Barnett shale, the most brittle sections were found to be those rich in silica and low in clay. These compositions are generally found by core analysis (Jacobi et al, 2008). Brittleness can be determined from the Young's Modulus, Poisson's Ratio, and Brinell hardness of the shale, all of which are determined from core samples (Kundert et al, 2009).…”
Section: Prospectingmentioning
confidence: 99%
“…Porosity and permeability are determined by core analysis or in-situ nuclear magnetic resonance. Other porosity measurements, such as acoustic and neutron-density methods, are affected by variations in composition and organic content of the reservoir rock and are therefore less accurate (Jacobi et al, 2008). Fracture orientation and density can be determined using Logging-WhileDrilling (LWD) imaging; this allows rapid decisions to be made regarding the direction of drilling and the potential efficacy of fracture stimulation (Quinn et al, 2008).…”
Section: Prospectingmentioning
confidence: 99%
“…Favorable intervals are usually the more siliceous lithofacies because they are geomechanically more brittle and, as a result, are good zones for fracture initiation. It has also been reported that there exists a strong relationship between the thermal maturity of the kerogen and the corresponding brittleness of the rock (Jacobi, et al, 2008), which makes targeting these lithofacies crucial for maximizing reservoir production. On the other hand, it is extremely crucial to avoid lithofacies that might act as fracture barriers due to their geomechanical makeup.…”
Section: Need For a Shale Gas Facies Expert Systemmentioning
confidence: 99%
“…A shale gas facies expert system has been developed (Jacobi, et al, 2008) incorporating an integrated petrophysical reservoirevaluation approach for characterizing shale gas reservoirs utilizing downhole wireline log measurements. An integrated petrophysical approach enables a comprehensive characterization of the reservoir in terms of its various properties.…”
Section: The Shale Gas Facies Expert Systemmentioning
confidence: 99%
“…Furthermore, understanding deformational properties becomes a fundamental task to better optimize operational procedures in shale gas reservoirs (Jacobi et al 2008;Britt and Schoeffler 2009;Sone 2012;Ghassemi and SuarezRivera 2012). Shales are the most ubiquitous sedimentary rock, and they have been characterized in the past.…”
Section: Introductionmentioning
confidence: 99%